2018
DOI: 10.1016/j.ssci.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Is it safe to cross? Identification of trains and their approach speed at level crossings

Abstract: • Drivers' perceptions of oncoming trains and decision making regarding their crossing behaviours were examined • Drivers identified the presence of trains 2km away and their movement at 1.6km away, with high variability between participants • Most participants underestimated the speed of oncoming trains, particularly when they were travelling at higher speeds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…This was also observed by the research team on the multiple occasions they visited the site. This is in line with the literature, which shows that drivers tend to underestimate speeds of large objects such as trains (Clark, Perrone, & Isler, 2013; Larue et al, 2018), and report that they would enter level crossings even when trains are very close to level crossings when sighting distances are very long (Larue et al, 2018), as at the trial site considered in this study.…”
Section: Discussionsupporting
confidence: 92%
“…This was also observed by the research team on the multiple occasions they visited the site. This is in line with the literature, which shows that drivers tend to underestimate speeds of large objects such as trains (Clark, Perrone, & Isler, 2013; Larue et al, 2018), and report that they would enter level crossings even when trains are very close to level crossings when sighting distances are very long (Larue et al, 2018), as at the trial site considered in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Most LCs around the world are passive. In Australia it is 67% of the total number of LCs and 75% in the USA [3]. In 2011, in the UK, 75% of all LCs were passive but in Belgium only 15% [4].…”
Section: Types Of Level Crossingsmentioning
confidence: 99%
“…Increased speeds of trains and vehicles on roads require greater sight distance for deciding whether to enter a LC or not. One of the main causes of crashes at LCs where there is a lack of barriers, is the behaviour of drivers who fail to judge correctly the speed and distance of approaching trains [3]. In 1996, the Transport Research Laboratory (UK) identified two categories of drivers that are most likely to be involved in accidents at LCs: drivers who believe that they have enough time to cross before train arrives, and do not stop or cannot stop because they are too close to the "stop line" when the amber light starts to flash, and drivers who are distracted or careless of the signals.…”
Section: Lc Accidents and Types Of Users Involvedmentioning
confidence: 99%
“…With regard to highway-railway grade crossing safety issues, several studies discuss various aspects of crossing safety (Saccomanno et al, 2004;Millegan et al, 2009;Chaudhary et al, 2011;Chadwick et al 2014;Tung et al, 2015;Wang et al, 2016a;Heydari et al, 2016b;Haleem, 2016;Liu and Khattak, 2017;Hsu and Jones, 2017;Sperry et al, 2017;Zhang et al, 2017;Larue et al, 2018;Beanland et al, 2018). Many grade crossing studies can be divided into two categories: (1) crash-frequency studies (Hauer and Persaud, 1987;Austin and Carson, 2002;Saccomanno and Lai, 2005;Park and Saccomanno, 2005;Oh et al, 2006;Yan et al, 2010;Medina and Benekohal, 2015;Heydari and Fu, 2015;Lu and Tolliver, 2016;Heydari et al, 2016a;Heydari et al, 2017b; Guadamuz-Flores and Aguero-Valverde, 2017); and (2) crash-consequence studies (Eluru et al, 2012;Hao et al, 2015;Ghomi et al, 2016;Zhao et al, 2018).…”
Section: Unobserved Heterogeneitymentioning
confidence: 99%